THE ROLE OF PRODUCT KNOWLEDGE, LIFESTYLE, AND HALAL AWARENESS IN SHOPPING INTENTIONS TO BUY HALAL PRODUCTS - Miskiyyah, Millatul; Muarif, Ahmad Dalhar (Journal of Islamic enterpreneurship and Management, 2022)
This study aims to analyze the influence of product knowledge, lifestyle, and halal awareness of the intention to buy halal products. This study uses primary data to obtain respondents by distributing questionnaires online. By distributing questionnaires there were 134 respondents who filled in the questions in the questionnaire in accordance with the indicators for each variable. Data processing in this study uses SPSS data version 16.0 by analyzing through the reliability test, regression test, and validity test. From the results of the SPSS results obtained have a significant effect on product knowledge, lifestyle, and halal awareness of the intention to buy halal products.